ANALISIS PEMBELAJARAN SEJARAHISU-ISU KONTROVERSIAL DI SMA - Saefudin, Arif; Hariyono, H.; Sariyatun, S. (Sebelas Maret University (UNS), 2016)
This study aims to (1) describe the planning; (2) describes the learning process; (3) identify the obstacles encountered by teachers in teaching history; (4) analyzing the efforts made by teachers of history to overcome obstacles in learning, and (5) determine the appreciation of learners in learning the history of a controversial issue. This research was conducted at SMA Negeri 1 Banyumas, using the form of qualitative descriptive study with a single case study research strategy spikes. The data source consists of speakers, events / activities, documents and archives. Data collection techniques using in-depth interview techniques, direct observation, and content analysis. The sampling technique used purposive sampling and time sampling. The validity of the data use triangulation of data, methods, and theory. Analysis of data using interactive analysis with three stages that occur bergayutan, namely data reduction, data presentation, and drawing conclusions / verification. The results showed that (1) in planning lessons, teachers make learning devices independently, but can not be separated from the sample that has been made in a top-down from the government; (2) execution history teaching of controversial issues still running half-hearted because of the mindset held by teachers is still in the stage of action and weak in re-actualization stage, so that learning becomes out of context; (3) obstacles in learning the history of a controversial issue consists of all aspects of planning, implementation, and other supporting factors in the learning process; (4) efforts to overcome the obstacles still limited in technical level, teachers have not been able to explore the concept because it is constrained by the environment and position; (5) appreciation of learners towards learning is very varied history of controversial issues, many of which have a material interest in the history of the controversial and potentially to train students to think critically to an event.